Effect of Aloe vera extract on some parameter liver functions changes and complete blood count induced by Azathioprine in male rats - Al-Hasnawi, Ahmed; Jasim, Wafaa Kadhim (Journal of Kerbala for Agricultural Sciences, 2023)
The present study aimed to reveal the biological vitality of the immune suppressant medicine azathioprine (AZA), which has been used to treat immunological illnesses like acute lymphoblastic leukemia (ALL), inflammatory bowel disease, and organ transplants, successfully lowers immune reactivity for liver and bone marrow. The goal of the current study was to evaluate the preventive effects of Aloe Vera extract in treating hematological and biochemical side effects brought on by azathioprine. Have been selected There were four groups of adult male rats. A mixture of azathioprine (50 mg/kg) and Aloe Vera (500 mg/kg) was given to group 4 in addition saline that group 1 received. Group 2 received azathioprine (50 mg/kg) orally for during a 30 days period. The findings show that azathioprine significantly reduced blood test results (RBC , WBC , PCV). While AST and ALT levels significantly increased in the biochemical test in contrast to the control group , Conclusions the Hepatotoxicity, or liver damage from immunosuppressive medications like azathioprine, is a possible side effect and Due to the damage that has happened to the hepatic tissue, the enzymes that assess the activities of the liver are raised.